In-Depth Insight into Corrosion Inhibition Performance of Sweet Potato Leaf Extract as a Green and Efficient Inhibitor for 6N01 Al Alloy in the Seawater Experimental and Theoretical Perspectives - Tang, Hong (Langmuir : the ACS journal of surfaces and colloids, 2024)
Corrosion protection of metal has become an important and urgent topic, which requires the development of an inexpensive, environmentally friendly, and highly efficient corrosion inhibitor. Herein, a sweet potato leaf extract (SPL) was obtained by a simple water-based extraction method and then as a green corrosion inhibitor for 6N01 Al alloy in the seawater was well investigated by the weight loss method and various electrochemical tests. Fourier transform infrared (FT-IR) and ultraviolet-visible (UV-vis) spectroscopies were carried out to investigate the compositions of SPL. The findings from the potentiodynamic polarization (PDP) curves suggest that SPL functions as a typical mixed-type corrosion inhibitor. Notably, the maximum corrosion inhibition efficiency reaches 94.6% following a 36 h immersion period at 25 °C. The adsorption behavior of SPL on the Al alloy surface belongs to the Langmuir adsorption isotherm. The Gibbs free energy value illustrates that the adsorption of SPL contains both physisorption and chemisorption. Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) indicate that SPL is firmly attached to the Al alloy surface by making a protective layer, which can effectively inhibit the corrosion of the Al alloy in the seawater. Furthermore, quantum chemical calculations were applied to validate the chemical adsorption and elucidate the relationship between the electronic structure of the active components in SPL and their effectiveness in corrosion inhibition